2019
DOI: 10.1107/s1600576719005569
|View full text |Cite
|
Sign up to set email alerts
|

Precession electron diffraction tomography on twinned crystals: application to CaTiO3thin films

Abstract: Strain engineering via epitaxial thin‐film synthesis is an efficient way to modify the crystal structure of a material in order to induce new features or improve existing properties. One of the challenges in this approach is to quantify structural changes occurring in these films. While X‐ray diffraction is the most widely used technique for obtaining accurate structural information from bulk materials, severe limitations appear in the case of epitaxial thin films. This past decade, precession electron diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…125 A very promising application of dynamical refinements is foreseen for such cases where the main goal is to point out subtle structural changes. Steciuk et al 76 showed that the structure of a thin film of CaTiO 3 grown on SrTiO 3 can be refined even in the presence of twinning and that the evolution of the thin film structure as a function of the distance from the substrate may also be observed.…”
Section: Applications In Materials Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…125 A very promising application of dynamical refinements is foreseen for such cases where the main goal is to point out subtle structural changes. Steciuk et al 76 showed that the structure of a thin film of CaTiO 3 grown on SrTiO 3 can be refined even in the presence of twinning and that the evolution of the thin film structure as a function of the distance from the substrate may also be observed.…”
Section: Applications In Materials Sciencesmentioning
confidence: 99%
“…Since 2007, the three-dimensional ED method has spread with an exponential trend. Very soon, still in the hand of few specialists, it allowed the structure determination of landmark samples, mostly inorganic, that were considered impracticable for X-ray methods. Later, the introduction of ultrafast data acquisition procedures and of more sensitive detectors allowed establishing robust experimental protocols also for organic and metalorganic materials. Finally, three-dimensional ED found successful applications for macromolecules and other structures of biologic interest. The growing attention on three-dimensional ED is confirmed by the number and impact of related publications in the very last year, and by the fact that this method has been considered one of the most important recent scientific breakthroughs …”
Section: Introductionmentioning
confidence: 99%
“…A possibility for such systems is precession electron diffraction, a technique coupled with transmission electron microscopy which allows solving the structure of thin-film materials (Steciuk et al, 2019;Rotella et al, 2015). Despite its potency in obtaining accurate structure models, this technique requires a tedious and destructive sample preparation process.…”
Section: Introductionmentioning
confidence: 99%
“…In the hkl reciprocal space sections, the diffraction data showed a mirror symmetry (Figure S10), which is incompatible with the structure model. All measured diffraction data showed the same twinning, which was used during the dynamical refinement [29]. Similarly to the ICR-10 structure, the atomic displacement parameters of the two ligand legs pointing towards the pores were substantially higher than those of the rest of the structure.…”
Section: Icr-11mentioning
confidence: 75%